The continuation of perceived deviance: independent confessional schools in Sweden 1795–2019 - Henrekson, Ebba (British Journal of religious education, 2023)
This article aims to contribute to the ongoing discussion on public religion by describing how independent confessional schools were established in Sweden (1795–2019) and by clarifying and deconstructing the dominant ideals that underpin school policy initiatives concerning religion, education, and independent confessional schools. I seek to answer the question: In what way do independent confessional schools appear problematic in relation to general school policy during the period 1795–2019? Employing both descriptive quantitative analysis using register data on independent confessional schools and critical policy analysis inspired by Bacchi’s WPR-approach (‘What’s the Problem Represented to Be’), this study shows that (1) independent confessional schools are not a new or growing phenomenon in Sweden and (2) throughout this study’s focal period, regardless of whether a religious or secular foundation was ascribed to Sweden’s public school system, independent confessional schools were perceived to deviate from public schools’ principal values.